Drying of Cataloglu Apricots: The Effect of Sodium Metabisulfite Solution on Drying Kinetics, Diffusion Coefficient, and Color Parameters - Kayran, Seda; Doymaz, Ibrahim (TAYLOR & FRANCIS INC, 2021)
The effect of temperature and pre-treatment on drying kinetics and color parameters of apricot was investigated. The apricots were dried at 50, 60, 70, and 80 degrees C and constant air velocity of 2.0 m/s in cabinet dryer. Sodium metabisulfite solution (8%, w/w) was applied to 10 min prior to drying process. It was observed that both the drying temperature and the pre-treatment affected the drying and color parameters. The drying times of pre-treated samples were 6.49-20% shorter than those of control samples. To select the most appropriate thin-layer drying model for drying treatments, 10 mathematical drying models were fitted to the experimental data. Midilli & Kucuk model satisfactorily described the drying kinetics of SMB and control apricots. Effective moisture diffusivity ranged from 6.85 x 10(-10) to 2.10 x 10(-9) m(2)/s for control, between 7.83 x 10(-10) and 2.49 x 10(-9) m(2)/s for SMB samples calculated using the Fick's second law. Activation energy was estimated by using an Arrhenius type equation and found to be 34.25 kJ/mol and 35.39 kJ/mol control and SMB samples, respectively.
Keywords: Apricot; color; drying; effective moisture diffusivity; mathematical modeling; Agriculture